2015
DOI: 10.1021/acscatal.5b00149
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Nanofiltration and Recycle of an Asymmetric Ketone Hydrogenation Catalyst

Abstract: The continuous nanofiltration and recycle of a ruthenium diphosphine/diamine catalyst for the asymmetric hydrogenation of α-tetralone is demonstrated in a small scale flow system. Batch experiments show that the catalyst can be recycled under hydrogen pressure. Subsequent transient packed bed experiments serve to characterize the reaction and inform the design of the recycle experiments. The total internal volume of the resulting system is ∼50 mL, making this pilot useful for testing catalyst recyclability via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 59 publications
(82 reference statements)
0
21
0
Order By: Relevance
“…From an industrial perspective [146,147], the development of highly active catalysts, i.e. high turnover number catalysts, at low costs and with possible applications in flow chemistry appear as the main goal to fulfil [148][149][150][151].…”
Section: Resultsmentioning
confidence: 99%
“…From an industrial perspective [146,147], the development of highly active catalysts, i.e. high turnover number catalysts, at low costs and with possible applications in flow chemistry appear as the main goal to fulfil [148][149][150][151].…”
Section: Resultsmentioning
confidence: 99%
“…Jensen and co‐workers demonstrated a small‐scale (∼50 mL) pilot flow system to study the viability of nanofiltration. The asymmetric hydrogenation of α‐tetralone was studied by using a diphosphine/diamine catalyst 8 under high‐pressure hydrogen in a batch reactor . The optimized reaction time was 40 min, and a high selectivity (97 % ee ) was obtained.…”
Section: Homogeneous Enantioselective Catalysis In Flowmentioning
confidence: 99%
“…This will cause too high cost in industrial production, so the recovery of homogeneous catalysts needs to be solved. In 2015, to study the viability of nanofiltration, Jensen and co‐workers demonstrated a small‐scale (∼50 mL) pilot flow system . To develop this flow system, they studied the first asymmetric hydrogenation of α‐tetralone using a diphosphine/diamine catalyst 3 under high pressure of hydrogen in a batch reactor.…”
Section: Continuous‐flow Hydrogenation Using Homogeneous Catalystsmentioning
confidence: 99%